2015
DOI: 10.1111/geoa.12094
|View full text |Cite
|
Sign up to set email alerts
|

Location and density of rain gauges for the estimation of spatial varying precipitation

Abstract: Accurate estimation of precipitation and its spatial variability is crucial for reliable discharge simula-tions. Although radar and satellite based techniques are becoming increasingly widespread, quantitative precipita-tion estimates based on point rain gauge measurement inter-polation are, and will continue to be in the foreseeable future, widely used. However, the ability to infer spatially distributed data from point measurements is strongly dependent on the number, location and reliability of meas-urement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…When grouping the events by the maximum measured hourly intensity of any rain gauge of each event as done in Figure 4 into four equally sized groups of events, it is apparent that more intense events show a much higher spatial variability than the less intense ones. This is supported by the results of Girons Lopez et al [43] who came to the same conclusion. This does not mean that the deviation is negligible for events with smaller intensities than 26 mm/h (see Figure 4a,b).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…When grouping the events by the maximum measured hourly intensity of any rain gauge of each event as done in Figure 4 into four equally sized groups of events, it is apparent that more intense events show a much higher spatial variability than the less intense ones. This is supported by the results of Girons Lopez et al [43] who came to the same conclusion. This does not mean that the deviation is negligible for events with smaller intensities than 26 mm/h (see Figure 4a,b).…”
Section: Resultssupporting
confidence: 77%
“…Using precipitation interpolations from a dense rain gauge network and comparing it to a combination of radar and rain gauge data Girons Lopez et al [43] showed a significant improvement of the catchment-average interpolation error by using higher measurement densities. This behavior was even more apparent for higher precipitation intensities.…”
Section: Number Of Gaugesmentioning
confidence: 99%
“…Precipitation is indeed the main input driving many if not most models of hydrological processes (McDonnell & Beven, ; Seibert & McDonnell, ). However, although we know that precipitation varies greatly in time and even over short distances in space (Girons Lopez, Wennerström, Nordén, & Seibert, ; Goodrich, Faurès, Woolhiser, Lane, & Sorooshian, ; Vieux, ), uniformity is often still assumed for small areas. This assumption applies not only to the precipitation amount but also to its isotopic composition (D and 18 O), which has become a common tool in tracer hydrological investigations (McGuire & McDonnell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall in center-west and northern Brazil is monitored through a relatively sparse rain gauge data network (15 or fewer rain gauges per 10 4  km 2 ), comparable to inland regions of South America; sub-Saharan Africa; and central, east, and southeast-Asia 25 . These low densities are likely to result in non-trivial differences between regional rainfall data products 26 (in Switzerland, rain gauge densities of >24 rain gauges per 1,000 km 2 were required to avoid density-dependent biases 9 ).
Figure 1Study region and locations of in - situ (IS) rainfall and streamflow gauges. Panel (a) shows the Amazon-Cerrado transition states of Brazil.
…”
Section: Introductionmentioning
confidence: 99%